CHANGES IN CHOLESTEROL CONTENT OF SOME TISSUES DUE TO STARVATION AND REFEEDING IN ALBINO RATS - KUMAR, SHAILENDRA; SINGH, AJAY KUMAR; SINHA, U.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
In the starved animals the plasma, liver and muscle cholesterol level significantly depletes. On refeeding, the plasma cholesterol level in short term starved rats (7 days) recover in a short time but tissue cholesterol in short and prolonged starved rats (15 days) take longer span of time for recovery to the normal level. Similar was the fate of plasma cholesterol level in prolonged starved rats.